Defining value-based objectives for ERP systems planning - May, Jeffrey (2013)
The planning and subsequent implementation of Enterprise Resource Planning (ERP) systems still present a significant challenge for most organizations. Although consulting firms and customer enterprises have been aquiring more experience and expertise in the field, the level of sophistication of these systems and their wide organizational and social impact frequently leads to failed ERP implementations. In an attempt to minimize these failure rates, this paper defines a set of value-based objectives that could be used to enrich the ERP systems planning process. ERP systems planning objectives grounded by stakeholder values can be used as a conceptual guide for enhancing the decision making processes involved in ERP projects. Using Keeney's value-focused thinking approach, a set of means and fundamental objectives was identified using data collected via in-depth interviews in three large European firms. The relationships and interdependancies among these objectives are also presented and provide a starting point for further research.